Imogene King's Theory-Based Telenursing to Improve Medication Compliance in Tuberculosis Patients: Telenursing Tuberculosis - Achmad Wahdi; Devangga Darma Karingga; Dewi Retno Puspitosari (Journal Of Nursing Practice, 2025)
Background: Tuberculosis (TB) is an infectious disease with a high health burden that requires patient compliance in taking anti-tuberculosis (ATD) medications. Non-compliance remains a barrier to successful therapy. Telenursing, an information technology-based service innovation, can be utilized to improve patient satisfaction, especially when developed based on Imogene King's nursing theory. Objective: Can telenursing based on Imogene King's theory improve medication adherence in TB patients? Methods: The study used a quasi-experimental design, with an intervention group receiving telenursing services based on Imogene King's theory and a control group receiving health promotion. Data on medication adherence were collected through observation and a medication adherence questionnaire. Data were analyzed using the Wilcoxon Signed Rank test. Results: The study showed that in the intervention group, the majority of respondents (66.6%) or 10 patients had high medication adherence. Conversely, in the control group, the majority of respondents (66.6%) or 10 patients had only moderate medication adherence. This indicates that telenursing based on Imogene King's theory is more effective than conventional health promotion in improving ATD adherence. Conclusion: Telenursing based on Imogene King's theory can improve medication adherence in TB patients through reciprocal interaction, therapeutic communication, and the achievement of shared goals between nurses and patients using the SETIA-TB application. The implementation of telenursing based on abortion theory is recommended to support the success of TB therapy and can serve as an innovative service model in the community.